Age-Dependent Shift of AMPA Receptors From Synapses to Intracellular Compartments in Alzheimer’s Disease: Immunocytochemical Analysis of the CA1 Hippocampal Region in APP/PS1 Transgenic Mouse Model - Martín-Belmonte, Alejandro; Aguado, Carolina; Alfaro-Ruíz, Rocío; Itakura, Makoto; Moreno-Martínez, Ana Esther; de la Ossa, Luis; Molnár, Elek; Fukazawa, Yugo; Luján, Rafael (Frontiers in Aging Neuroscience, 2020)
The major structural correlate of the memory deficits and related symptoms of Alzheimer disease (AD) are mainly attributable to synaptic failure in both animal models and AD patients. Given the predominant roles of synaptic AMPA receptors (AMPARs) in excitatory synaptic transmission in the brain, changes in their dynamic regulation are also implicated in the pathophysiology of AD. Here, we used immunolocalisation techniques to analyse the expression and subcellular distribution of AMPARs in the hippocampal region of APP/PS1 mouse model of AD. Immunoblots and histoblots revealed that the total amount of AMPARs and their regional expression pattern in the hippocampus was similar in APP/PS1 mice and in age-matched wild type mice. At the ultrastructural level, two synapse populations were examined using SDS-digested freeze-fracture replica labelling in the stratum radiatum in mice: i) on spines of CA1 pyramidal cells; and ii) on randomly found dendritic shafts of CA1 interneurons. While one- and six-months-old APP/PS1 mice exhibited no change, we observed a significant reduction in synaptic AMPARs at 12 months of age in the two populations of synapses compared to wild-type mice. This reduction of AMPARs in dendritic spines was accompanied by a significant increase in AMPAR subunit proteins identified in intracellular compartments. Our data demonstrate an age-dependent reduction of synaptic AMPARs in APP/PS1 mice, which may contribute to impaired learning and memory at later stages of AD.